The ineffective emotion regulation of deaf college students: an ERP study - Dong, Qi; Sun, Le; Du, Xue (Frontiers in Human Neuroscience, 2024)
Deaf students have more difficulties with emotion regulation due to their hearing loss.They are suffering higher socio-emotional risk than the hearing person. But there are few studies explored the neural mechanisms of impaired emotion regulation in the deaf college students.30 hearing college students and 27 deaf college students completed the emotion regulation task while recording ERP data and subjective emotion intensity. Behavioral results found that deaf college students had higher emotional experience intensity compared to healthy controls. The ERP results showed the deaf college students had lower LPP amplitudes both using reappraisal and suppression strategies. Moreover, the LPP of expression suppression was associated with the increase of depression scores among deaf college students. Deaf college students may have impaired emotion regulation so that they are more accustomed to using expression suppression strategies to regulate their negative emotions which lead to high risk to be depression.